CWPO Degradation of Natural Organic Matter: Synthetic Water vs. Real Surface Water - Galeano, Luis Alejandro; García, Ana María; Torres Palma, Ricardo A. (2021)
H2O2 was slightly more efficiently used by the catalytic system on RW, in goodagreement with the highest percentage of color removal on this sample (~ 93 %);however, the NOM mineralization was significantly higher (75 %) on the SWagainst RW (37%). It probably was related with higher fraction of more refractoryhydrophilic substances formed in the real water (SUVA~ 3, HPI: 12.37 %, HPO:30.88 %) vs. synthetic water (SUVA>4, HPI: 2.30 %, HPO: 14.63 %). Finally, theHPO fraction significantly decreased in both waters, but in RW the change was lesssignificant due to the presence of more refractory substances than SW.